Heterologous Expression of Laccase1 from Cryphonectria parasitica in Saccharomyces cerevisiae - Kum-Kang So; Fatima Alejandra Hernandez Alvarado; Gui-Hwan Han; Jeong-Won Kim; Tae-Geum Kim; Dae-Hyuk Kim (Mycobiology)
Laccases are enzymes capable of oxidizing phenolic compounds and are important tools in different industrial processes. Heterologous expression of laccases is of great interest in biotechnological applications but achieving high expression levels is challenging. Three different laccases have been identified in the chestnut blight fungus Cryphonectria parasitica, among which a tannic acid-inducible laccase (laccase3) was successfully expressed using Saccharomyces cerevisiae. To obtain high and stable expression of fungal laccases, we cloned the gene encoding an extracellular laccase (Laccase1) of C. parasitica into a yeast episomal vector, used the resulting vectors to transform S. cerevisiae, and optimized the culture conditions of the selected transformants for Laccase1 production. We also tested the significance of the signal peptide of Laccase1 in the secretion of expressed Laccase1 and compared it with the widely used rice amylase signal peptide. Among the four constructs tested using a yeast episomal vector, full-length Laccase1 containing an endogenous signal peptide, showed the highest laccase activity. Interestingly, the stability of the recombinant vector expressing laccase was lower than that of the mock transformant, suggesting a detrimental effect of the Laccase1-expressing vector on host cells. Thus, we optimized the culture conditions to produce Laccase1 and the resulting optimum culture conditions identified through one-factor-at-a -time (OFAT) were 2% sucrose; 3% yeast nitrogen base without amino acid; pH 5.0; and 30 °C. The laccase activity was found to be 2.2 U/mL in optimal culture conditions, resulting in a 6.5-fold increase compared to the conventional culture medium.